Persepsi Taruna terhadap Pelaksanaan E-learning di Politeknik Penerbangan Makassar - Erna Wahyu P., Agnes; K., Munawir (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
This study aims to determine the perceptions of cadets towards e-learning learning using the Learnin Management System which has been facilitated by campuses and online learning, the advantages and disadvantages of e-learning, whether the teaching materials delivered by lecturers can be understood by cadets / cadets, and the perceptions of cadets. taruni towards online learning itself. This research is a quantitative descriptive study. The subjects of this study were all cadets of the Makassar Aviation Polytechnic cadets during the Covid-19 pandemic. This study uses data from the results of a questionnaire distributed to all cadets of 398 cadets using Google form, making it easier for researchers to collect and process data. From the results of data analysis, it was found that cadets of Makassar Aviation Polytechnic cadets showed enthusiasm in using e-learning and online, especially in theory courses. Taruna feel more enthusiastic and understand more about the material presented by the lecturer because e-learning is more varied and less boring and more interactive in learning. But it does not apply to practical courses, which require cadets to practice directly what the lecturer has conveyed in theory. So that cadets find it difficult to do direct practice.